An Ethnography Study of Stress Management among Sundanese, Chinese, and Javanese - Fadhilah, Savira Maghfiratul; Heikal, Jerry; Savitri, Fania Mutiara; Mangkuto, Shidiq Umar; Saputra, Tubagus Chandra (Universitas Islam Sultan Agung, 2024)
This ethnographic study examines how the cultural backgrounds influence stress management among Sundanese, Chinese, and Javanese officers in the Directorate General of X. Through a qualitative ethnographic approach, data were gathered via in-depth interviews, observations, and document analysis to uncover the unique stress management methods employed by each cultural group. The findings demonstrate that Sundanese officers focus on work-life balance and rely on supportive social networks, guided by the values of